Analysis of the Influence Dow Jones Islamic Index and Macroeconomic Variables on the Jakarta Islamic Index - Laleno, Farazdaq; Fadli, Faishal (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2025)
This research seeks to examine the effect of the Dow Jones Islamic Index and macroeconomic variables on the Jakarta Islamic Index (JII) over the period from March 2019 to March 2024. A quantitative method is applied using the Error Correction Model (ECM) to explore both short-term dynamics and long-term equilibrium relationships among the variables. The findings indicate that, in the long run, DJIUS has a significantly negative influence on JII, while DJICHK exerts a significantly positive impact. Additionally, the COVID-19 dummy variable shows a notable negative effect. In the short run, however, none of the independent variables exhibit a significant effect on JII, although the significance of the error correction term (ECT) shows significant results.